2020
DOI: 10.1016/j.ecolmodel.2020.109049
|View full text |Cite
|
Sign up to set email alerts
|

A box-model of carrying capacity of the Thau lagoon in the context of ecological status regulations and sustainable shellfish cultures

Abstract: Highlights► The variability of oyster production is mainly controlled by the hydrometeorology. ► Waste water treatment plant (WWTP) efficiency affect oyster production, without significantly improving the ecological status of the Thau lagoon. ► Scenario of oyster stocking density to its authorized maximum triggered an increase of oyster productions at the expenses of thinner oysters with a lower condition index. ► The Thau lagoon remains an exceptional site for oyster farming associated with "good" ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…To reach a satisfactory trade-off between uses, ecosystem services and maintaining biodiversity and ecological functions under global change, there is a need to use ecosystem-based models (Filgueira et al 2015;Guyondet et al, 2014;McKindsey et al, 2006). Such a model has been developed for Thau lagoon and showed that lagoon productivity significantly depends on hydrometerology, with higher oyster production in wet years than in dry years (Pete et al, 2020).…”
Section: Management Of Restoration and Shellfish Farmingmentioning
confidence: 99%
“…To reach a satisfactory trade-off between uses, ecosystem services and maintaining biodiversity and ecological functions under global change, there is a need to use ecosystem-based models (Filgueira et al 2015;Guyondet et al, 2014;McKindsey et al, 2006). Such a model has been developed for Thau lagoon and showed that lagoon productivity significantly depends on hydrometerology, with higher oyster production in wet years than in dry years (Pete et al, 2020).…”
Section: Management Of Restoration and Shellfish Farmingmentioning
confidence: 99%
“…The development of tools to evaluate "assimilative carrying capacity" is listed as an action plan in the new Strategic Plan for Sustainable Aquaculture 2021-2027. Other French studies developed a modeling tool to evaluate the effect of nitrogen and phosphorus inputs into the Thau Lagoon on oyster stocking densities and oyster performances, and the impact of stocking density on phytoplankton depletion and the ecological status of the lagoon based on metrics of dissolved inorganic nitrogen and phosphorous, and total nitrogen and phosphorous [104,105]. Despite the funding of ECC projects, French policy does not explicitly include ECC.…”
Section: Discussionmentioning
confidence: 99%
“…To consider such interventions, management of sea channel openings or other actions, multi-factorial modelling can be a helpful tool to design potential scenarios and the reactions of ecosystems (e.g. GAMELag, Pete et al 2020). Our work is hence a valuable contribution for the potential application of this kind of modelling on small-surface lagoons, since this requires a deep knowledge base of the studied systems and of their responses towards local and global change (Gunaratne et al 2011;Jones et al 2018;Doughty et al 2019;Pérez-Ruzafa et al 2019;Teixeira and Solari 2020).…”
Section: Small Lagoons In the Larger-scale Context And Management Per...mentioning
confidence: 99%